MAKING PROTOTYPE DYE-SENSITIZED SOLAR CELLS (DSSC) BASED ON TiO2 NANOPORY USING EXTRACTION OF MANGOSTEEN PEEL (Garnicia mangostana) - Hardani, Hardani; Hidayatullah, Alpiana; Angraini, Lily Maysari (Indonesian Physical Review, 2018)
Dye-sensitized solar cell (DSSC) is one of the photochemical electrical cells consisting of a photoelectrode, dye, electrolyte, and counter electrode. The manufacture of prototype Dye-sensitized solar cell (DSSC) utilizes carotene from the dye extract of mangosteen peel pigment (Garnicia mangostana). This study aims to create a Dye-sensitized solar cell (DSSC) and know the efficiency it produces. This Dye-sensitized solar cell (DSSC) consists of a pair of FTO (Flour-doped in oxide) glass intercepts facing each other. The glass acts as an electrode and counter electrode and separated by a redox electrolyte (I- / I3-), arranged to flank each other to form a wafer. In the electrode, is deposited a porous nanocrystalline TiO2 layer, as well as dye extract of mangosteen peel pigment (Garnicia mangostana). While on the counter electrode coated with a layer of platinum. This article presents some experimental data on absorbance properties and the conductivity of dye extract of mangosteen peel pigment (Garnicia mangostana) as an application in DSSC. Absorbance test using Spectrophotometer UV Visible 1601 PC and electrical properties test using Elkahfi 100 / Meter I-V. DSSC fabrication has been done using dye extract of mangosteen peel pigment (Garnicia mangostana) with coating spin coating technique. The results showed that the dye extract of mangosteen peel pigment (Garnicia mangostana) had an absorbance spectrum of 380-520 nm range. From the test results using AM 1.5G solar simulator (100 mW / cm2), it was found that the volume of TiO2 precursors affected the performance of DSSC solar cells and the overall conversion efficiency was 0.092%.